A prisoner of birth [large type] - Archer, Jeffrey, 1940- (Center Point Pub., 2008)
A man framed for the murder of his best friend seeks revenge against the four men who put him in Belmarsh prison, the highest-security jail in the land, from where no inmate has ever escaped.